2001
DOI: 10.1136/oem.58.11.735
|View full text |Cite
|
Sign up to set email alerts
|

The role of cumulative physical work load in lumbar spine disease: risk factors for lumbar osteochondrosis and spondylosis associated with chronic complaints

Abstract: Objectives-To investigate the relation with a case-control study between symptomatic osteochondrosis or spondylosis of the lumbar spine and cumulative occupational exposure to lifting or carrying and to working postures with extreme forward bending. Methods-From two practices and four clinics were recruited 229 male patients with radiographically confirmed osteochondrosis or spondylosis of the lumbar spine associated with chronic complaints. Of these 135 had additionally had acute lumbar disc herniation. A tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
69
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(75 citation statements)
references
References 40 publications
5
69
0
1
Order By: Relevance
“…These forces, however, are exerted on the low back for several hours each day thereby resulting in high cumulative force over many years of activity, which have been reported to increase the risk of developing a low-back disorder [10]. In addition, a recent experimental study has shown that static lumbar flexion, which occurs during extreme trunk flexion, is a risk factor for developing a low-back disorder [17].…”
Section: Risks Associated With Pliers Tyingmentioning
confidence: 99%
See 1 more Smart Citation
“…These forces, however, are exerted on the low back for several hours each day thereby resulting in high cumulative force over many years of activity, which have been reported to increase the risk of developing a low-back disorder [10]. In addition, a recent experimental study has shown that static lumbar flexion, which occurs during extreme trunk flexion, is a risk factor for developing a low-back disorder [17].…”
Section: Risks Associated With Pliers Tyingmentioning
confidence: 99%
“…Spinal disc pressure is known to vary depending on the amount and type (e.g., forward, sideward, twisting) of bending and external loads [10].…”
Section: Data Analysis Methodsmentioning
confidence: 99%
“…There is some evidence of an association of back symptoms with objective (eg, radiological) findings of the spine (30)(31)(32). However, health care use cannot, nor can indeed any data that comprise symptoms as a component of case definition, refute the possibility that, in heavy work, symptoms are more disturbing than in light work (33).…”
Section: Discussionmentioning
confidence: 99%
“…1). Stud welding requires frequent bouts of prolonged stooping (Fethke et al, 2011), a posture that can lead to an elevated risk of low back pain (Punnett et al, 1991;Seidler et al, 2001;Jansen et al, 2004).This posture also frequently places the breathing zone in the buoyant plume of the welding fume (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%